2015
DOI: 10.4187/respcare.03996
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula and Aerosolized β Agonists for Rescue Therapy in Children With Bronchiolitis: A Case Series

Abstract: Asthma and bronchiolitis are episodic obstructive pulmonary diseases characterized by bronchoconstriction, airway wall inflammation, increased mucus production, and air-flow obstruction. We present the cases of 5 infants treated for acute bronchiolitis with respiratory distress using a combination of high-flow nasal cannula oxygen (HFNC) and an Aerogen nebulizer to deliver aerosolized ␤-agonist therapy. In all infants, we found that HFNC resulted in a greater heart rate increase than delivery via a facemask. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…The use of a non‐human primate animal model, in the weight range of a full‐term newborn human, enabled us to make radiolabeled measurements in a highly relevant model, however results will need to be confirmed in the clinical setting. The present study results, combined with recent favorable case reports set out the rational for the scientific relevance of such a clinical investigation to be conducted in infants and toddlers. Beyond the commercially available cannulas tested in the present study, prototypes of streamlined components for aerosol delivery during NHF offer promising prospects for the development of this technique …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The use of a non‐human primate animal model, in the weight range of a full‐term newborn human, enabled us to make radiolabeled measurements in a highly relevant model, however results will need to be confirmed in the clinical setting. The present study results, combined with recent favorable case reports set out the rational for the scientific relevance of such a clinical investigation to be conducted in infants and toddlers. Beyond the commercially available cannulas tested in the present study, prototypes of streamlined components for aerosol delivery during NHF offer promising prospects for the development of this technique …”
Section: Discussionmentioning
confidence: 62%
“…Jet nebulization with a facemask placed on top of the nasal cannula was also associated with low lung deposition (0.5% and 0.03% of the nebulizer charge in the in vitro 9‐month‐old toddler and in vivo full‐term newborn infant models, respectively). Those results may explain the therapeutic failure reported by Morgan et al nebulizing on top of NHF cannula as a rescue therapy in the clinical setting . Beyond high gas flow driven aerosol impaction (6 L/min jet nebulization plus 2 L/min NHF therapy), two phenomena may contribute to the low aerosol delivery in this condition: (1) the physical nasal obstruction caused by the cannula and (2) the excess NHF flow‐rate beyond the patient's inspiratory flow requirement and thus associated with gas leakage at the cannula/nostril interface and washout of the oral cavity in case of open mouth breathing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clinically, bronchiolitis patients always need to inhale bronchodilator during HFNC . However, for those patients, aerosol delivery becomes a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The mounting observations of response and clinical evidence in combination with its ease of use and patient tolerability have resulted in increasing adoption of HFNT, with particular interest in concurrent aerosol delivery during HFNT [6][7][8][9][10]. Morgan et al showed that infants with acute bronchiolitis tolerated aerosolized b-agonist therapy better during HFNT than with a facemask, possibly preventing them from escalating to more invasive respiratory support [11]. In vitro studies indicate that aerosols can be efficiently delivered during HFNT [12,13].…”
Section: Introductionmentioning
confidence: 99%